Gender, perceptual factors, and entrepreneurial intention: Evidence from Egypt - El-Hadary, Eman Tawfik (AUC Knowledge Fountain, 2018)
In Egypt, women's total early-stage entrepreneurial activity is 3.7% out of female adult population coupled with one of the world's lowest women's economic participation rate. As the government is no longer the haven for women's jobs and the private sector is not filling the void, promoting entrepreneurship amongst women can prove effective in creating employment opportunities as well as empowering women with financial and social autonomy to allow them to become equal decision maker within the family and or household. In this research, the relationship between gender and entrepreneurial intention among non-entrepreneurs was investigated. The research shed light on the possible reasons of why women are less likely to start their own business compared to men. There is a body of literature that argues that the perceptual factors, namely self-efficacy, fear of failure, ability to recognize opportunities, and knowing an entrepreneur, might be the answer. Therefore, this thesis established a mediation analysis using a nationally representative sample data of the Global Entrepreneurship Monitor in Egypt from 2008 to 2015 to investigate if perceptual factors mediate the relationship between gender and entrepreneurial intention. This study validated the hypotheses among the non-entrepreneurs showing that the relationship between entrepreneurial intention and gender is mediated by the perceptual factors investigated in this thesis.